Efektivitas Pengajaran Akhlak Dalam Mata Pelajaran PAI Terhadap Perilaku Siswa Di SMK Muhammadiyah 2 Boja - Widodo, Dwi Adhi; Hadi, Syaiful (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to analyze how effective the teaching of morals in Islamic Religious Education subjects is on student behavior at SMK Muhammadiyah 2 Boja. Using a qualitative approach with a case study method, data were collected through observation, interviews, and documentation involving Islamic Education teachers and students as research subjects. The results revealed that the teaching of morals in PAI has a significant influence on students' character building, especially in terms of discipline, responsibility, and social ethics. However, the effectiveness of this teaching is influenced by several factors, including teaching methods, the role of teachers, and support from the school environment. Therefore, it is important to innovate in learning strategies and establish closer collaboration between schools and parents to improve the effectiveness of moral teaching.